OPTIMASI KONDISI PROSES PEMBUATAN NANOEMULSI MINYAK SERAI WANGI DENGAN METODE TAGUCHI SEBAGAI ANTIJAMUR PADA CAGAR BUDAYA - Lisa Dwi Hanifah; Mokhammad Fajar Pradipta; Nahar Cahyandaru (Balai Konservasi Borobudur Magelang, 2022)
This research aims to determine the effect of parameters on characteristic and increase stability; determine the optimum conditions to get the best nanoemulsion characteristic in the form of the smallest droplet size; find out the effectivity to inhibit Aspergillus fumigatus growth and to kill Lichens. The nanoemulsion formulation was made by using Spontaneous Emulsification of Low Energy method and it was designed by Taguchi statistical method. The parameter of analysis are organoleptic, pH, thermal stability test, freeze-thaw cycle, mechanical stability test, turbidity, polydispersity index (PdI), and particle size test. The antifungal test was carried out by applying nanoemulsions in a laboratory scale to Aspergillus fumigatus and in natural cultures by spraying nanoemulsions directly on lichen in Borobudur Temple rocks off. Nanoemulsion was successfully obtained with droplet sizes of 13.40-28.97 nm. The SNES ratio and the stirring rate had an effect on resulting nanoemulsion, while the stirring time had a less significant effect. The optimum conditions for making nanoemulsions were obtained which resulted in the best composition in a form of the smallest droplet size (13.11 nm with PdI value of 0.337), namely at SNES ratio 1:8:1, time of 5 minutes, with stirring speed of 2800 rpm. This formula resulted in a minimum inhibitory concentration against Aspergillus fumigatus growth as an estimate of lemongrass oil. Nanoemulsion with a minimum concentration of oil 2.5% was effective to kill lichens and inhibit the growth of new lichens.